EXPLORING EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN PRIMARY SCHOOL SETTINGS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Teaching English to young learners poses significant challenges that require the implementation of effective learning methodologies to ensure student engagement and motivation throughout the educational process. The primary objective of this thesis is to identify the teaching strategies employed by a fifth-grade English teacher and to explore the obstacles encountered while teaching English to young learners. The findings revealed that the teacher utilized eight distinct strategies when teaching English, including listen and repeat, listen and do, question and answer, in-pair activities, cooperative learning, and educational games. Additionally, the study identified specific challenges faced by the teacher, namely the lack of teaching resources and a limited understanding of Teaching English to Young Learners (TEYL) strategies. These obstacles stem from the teacher's insufficient knowledge in catering to the needs of young English learners and the scarcity of teaching materials available within the school environment.